Penindasan Kelompok Minoritas dalam Lagu - Hanifa Dwipinasti Sakina; Alex Sobur (Bandung Conference Series: Journalism, 2022)
Abstract. This undergraduate thesis is a critical discourse dissection with the lyrics of “Kafir” written by Jason Ranti as its object. In this critical discourse analysis, the lyrics of “Kafir” is analyzed to unveil the form of violence in the social life. The form of violence can be symbolically or not and even both of them. In the lyrics of “Kafir” there is a discourse analysis that wants to develop the knowledge and in opposition with the form of power that dominant. The problem in the lyrics of “Kafir” is not value-free because it is link with a social problem that occurs in the society and in the interfaith people. Through critical discourse analysis with the lyrics of “Kafir” written by Jason Ranti, raise a knowledge of the symbolic dominance and unsymbolic dominance that people of minority experience with, and emerge critical consciousness with unveil the forms of power and the power relations itself: domination, oppression, and discrimination from the people of majority. This research has a purpose to expose the critical discourse within the lyrics of “Kafir” as a form against power relations and domination by showing that there is a form of violence in the name of faith or religion which people will allow themselves to do everything in the name of religion, in which raise a problem when the religion become a tool to dominate and oppress minority people. Abstrak. Skripsi ini merupakan pembedahan secara kritis dengan lirik lagu “Kafir” yang ditulis oleh Jason Ranti sebagai objeknya. Dalam analisis wacana kritis ini, lirik lagu “Kafir” dianalisis untuk menyingkap bentuk kekerasan dalam kehidupan sosial, ketidakberesan yang ada dalam tatanan sosial. Bentuk kekerasan tersebut bisa berupa simbolis atau kelihatan jelas bahkan keduanya. Dalam lirik lagu “Kafir” terdapat aktivitas wacana yang ingin menghasilkan pengetahuan untuk melawan bentuk kuasa yang dominan. Persoalan dalam lirik lagu “Kafir” tidak bebas nilai karenanya berkelindan dengan ketidakberesan sosial yang terjadi dalam kehidupan bermasyarakat dan berkehidupan antar umat beragama. Melalui analisis wacana kritis dalam lirik lagu “Kafir” muncul pengetahuan mengenai dominasi simbolis dan tak simbolis yang dirasakan juga dialami oleh orang-orang yang minoritas, dan menumbuhkan kesadaran kritis dengan menyingkap bentuk-bentuk kuasa: dominasi, penindasan, diskriminasi yang dilakukan oleh orang-orang yang mayoritas. Penelitian ini bertujuan mengungkap wacana dalam lirik lagu “Kafir” sebagai suatu bentuk perlawanan dari bukti adanya kekuasaan yang dominan dengan memperlihatkan adanya bentuk kekerasan atas nama kepercayaan atau agama, yang mana semua orang sudi melakukan apapun atas nama agama yang menjadikannya berbuah persoalaan jika agama menjadi alat untuk mendominasi kepercayaan-kepercayaan lain yang minoritas dan yang lebih pentingnya bahwa semua orang ikut terlibat dalam struktur kekerasan tersebut.